Nonlinear companding transform for PAPR reduction in lattice-OFDM system - Si-ming PENG; Yue-hong SHEN; Zhi-gang YUAN; Yu-wei MIAO; Wei JIAN (Tongxin xuebao)
Since the inherent higher peak-to-average power ratio (PAPR) in lattice OFDM (LOFDM) is higher than that of conventional OFDM systems, a novel continuous and differentiable nonlinear companding scheme is investigated and analyzed when employing the conventional companding transforms. By making full use of the characteristic of the Gaus-sian-distributed original signals and employing a truncation to the distribution function of the original signals, the com-panded signals can be restricted in a specific region which consistents with the distribution of original signals. Therefore, the companded signals can not only achieve an improved PAPR and bit error ratio (BER) performance but also maintain the statistical characteristics of the original signals. Theoretical analysis and simulation results demonstrate that the pro-posed scheme substantially outperforms the conventional nonlinear companding schemes.